A Systematic Review on the Relationship of Bisphenol-A with PCOS, with a Focus on Pakistan - Ghazala Shaheen Tariq; Fozan Ahmed; Shafaq Bushra; Seemin Kashif (JLUMHS)
The study was done to show the association of high bisphenol-A levels with polycystic ovarian syndrome, keeping Pakistan in focus. Google Scholar, PubMed, ScienceDirect, and DOAJ were used for the literature search. Original research articles from 2018 to 2023 were included in this review. A total of 86 articles were extracted. After exclusion, fourteen (16) articles were included in the review. No human studies were found in Pakistan, the USA, Canada, Australia, or Europe. All studies included in the review were case-control studies. Most of these studies (14) showed a positive relationship between BPA levels and PCOS, but two studies could not. No animal or human studies were found in Pakistan. Only one study was found in humans in Pakistan, which showed a direct relation between BPA levels in urine and insulin resistance in diabetic patients. According to global studies, BPA was a possible etiological factor for PCOS. No such data was obtained from Pakistan, but evidence of high levels of BPA in tap water and various canned and bottled drinks in Pakistan was found. BPA should be considered an actual threat in Pakistan at the national level. So, studies must be done, and regulations must be made to control BPA use.